THE INFLUENCE OF ENTREPRENEURIAL EDUCATION AND FAMILY BACKGROUND ON ENTREPRENEURIAL INTENTION THAT IS MODERATED BY GENDER - Andani, Charlie; Puspitowati, Ida (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to determine the impact of entrepreneurship education and family background on entrepreneurial intentions in UNTAR students with gender as moderation. The technique of taking elements in this research uses non-probability sampling with a convenience sampling approach. Elements in this research are students who are currently pursuing an undergraduate degree at UNTAR with a total of 200 people. Data were calculated using the PLS-SEM approach. The results of this research explain that entrepreneurship education and family background have an increasing and significant impact on the intention to become an entrepreneur in UNTAR students. Gender positively moderates entrepreneurship education and family background on the intention to become an entrepreneur in UNTAR students.